2018
DOI: 10.1038/s41598-018-20387-0
|View full text |Cite
|
Sign up to set email alerts
|

Movement Strategies for Countermovement Jumping are Potentially Influenced by Elastic Energy Stored and Released from Tendons

Abstract: The preferred movement strategies that humans choose to produce work for movement are not fully understood. Previous studies have demonstrated an important contribution of elastic energy stored within the Achilles tendon (AT) during jumping. This study aimed to alter energy available for storage in the AT to examine changes in how jumpers distribute work among lower limb joints. Participants (n = 16) performed maximal and sub-maximal jumps under two paradigms, matched for increasing total work output by manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…Rigid-body modeling tracks individual segments within the body; however, this method requires complex data processing, commonly uses generic geometry scaling, ignores soft tissue deformation 16 and often combines the head, arms, and trunk to form a single segment. 1,9,17 The hybrid method calculates heel-lift from marker-based video tracking and therefore only requires force plate data to be integrated once to calculate flight distance, reducing errors due to integration drift while eliminating the need for complex data processing. As this method combines two separate measurements, it is critical that data are synchronized accurately.…”
mentioning
confidence: 99%
“…Rigid-body modeling tracks individual segments within the body; however, this method requires complex data processing, commonly uses generic geometry scaling, ignores soft tissue deformation 16 and often combines the head, arms, and trunk to form a single segment. 1,9,17 The hybrid method calculates heel-lift from marker-based video tracking and therefore only requires force plate data to be integrated once to calculate flight distance, reducing errors due to integration drift while eliminating the need for complex data processing. As this method combines two separate measurements, it is critical that data are synchronized accurately.…”
mentioning
confidence: 99%
“…Muscle work may be increased by increasing muscle force, increasing muscle contractile length change (fibre or fascicle length change) or a combination of the two. Our previous study demonstrated that when mass was added there was an increase in peak Achilles tendon force and peak ankle moment compared with when achieving the same work output by increasing jump height (Wade et al, 2018). We postulated that the additional net work produced at the ankle in the added mass paradigm was probably due to increased force production by plantar flexor muscles.…”
Section: Introductionmentioning
confidence: 93%
“…In our previous study, net work about the hip increased similarly in the two paradigms to meet increasing net work demands. In contrast, net work at the ankle was increased to a greater extent in the added mass paradigm, which we believe is due to the influence of the compliant Achilles tendon on muscle contractile mechanics (Wade et al, 2018). To investigate this, and therefore understand the factors influencing control strategies, the underlying muscle mechanics must be examined.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations